What's wrong with global challenges?. Issue 1 (2nd January 2022) - Ludwig, David; Blok, Vincent; Garnier, Marie; Macnaghten, Phil; Pols, Auke
ABSTRACT: Global challenges such as climate change, food security, or public health have become dominant concerns in research and innovation policy. This article examines how responses to these challenges are addressed by governance actors. We argue that appeals to global challenges can give rise to a 'solution strategy' that presents responses of dominant actors as solutions and a 'negotiation strategy' that highlights the availability of heterogeneous and often conflicting responses. On the basis of interviews and document analyses, the study identifies both strategies across local, national, and European levels. While our results demonstrate the co-existence of both strategies, we find that global challenges are most commonly highlighted together with the solutions offered by dominant actors. Global challenges are 'wicked problems' that often become misframed as 'tame problems' in governance practice and thereby legitimise dominant responses.